CONTEMPORARY TRENDS AND ISSUES IN ISLAMIC EDUCATION MANAGEMENT (A Literature Review) - Faisal DahrulSalihin (JURNAL HURRIAH: Jurnal Evaluasi Pendidikan dan Penelitian, 2025)
This study aims to identify and analyze emerging trends and contemporary issues in Islamic educational management practices. In the era of globalization and digitalization, Islamic educational institutions face various challenges and opportunities that influence educational management policies, strategies, and implementation. This study uses a qualitative approach with a library research method of analyzing relevant scientific literature. The results of the study indicate that current trends in Islamic educational management include digitalization of management, integration of Islamic values with modern management principles, and increasing the professionalism of educators. Prominent contemporary issues include the quality gap between institutions, weak strategic leadership, and minimal managerial innovation. This study is expected to provide a conceptual contribution to the development of adaptive and sustainable Islamic educational management practices